2015
DOI: 10.1021/acsmedchemlett.5b00169
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chalcone–Thiazole Hybrids as Potent Inhibitors of Drug Resistant Staphylococcus aureus

Abstract: A series of novel hybrids possessing chalcone and thiazole moieties were synthesized and evaluated for their antibacterial activities. In general this class of hybrids exhibited potency against Staphylococcus aureus, and in particular, compound 27 exhibited potent inhibitory activity with respect to other synthesized hybrids. Furthermore, the hemolytic and toxicity data demonstrated that the compound 27 was nonhemolytic and nontoxic to mammalian cells. The in vivo studies utilizing a S. aureus septicemia model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Sashidhara et al [31] suggested the procedure regarding this assay: The human blood was collected in a container of EDTA (2 mg mL −1 ). The resulting suspension was centrifuged at 800×g for 10 min to separate buffy coat and plasma.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…Sashidhara et al [31] suggested the procedure regarding this assay: The human blood was collected in a container of EDTA (2 mg mL −1 ). The resulting suspension was centrifuged at 800×g for 10 min to separate buffy coat and plasma.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…[ 7 ] However, these emerging resistances could be overcome by the synthesis and modification of new biologically active molecules. Several researchers have demonstrated a broad spectrum of biological activities of the 2‐aminothiazole (2‐AT) derivatives as antibacterial, [ 8 ] antifungal, [ 9 ] antitumoral, [ 10 ] antimalarial, [ 11–13 ] antidiabetic, [ 14 ] anti‐inflammatory, [ 15 ] and antiviral [ 16 ] agents (Figure 1). Many authors have suggested that the 2‐AT moiety may be used for fragment‐based drug discovery strategy, because it plays an important role in the treatment of different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of thiazole and pyrazole nucleus in different organic structures leads to potent biological activities such as anticancer [13][14], antimicrobial [15][16][17], anti-inflammatory, and antioxidant [18], antidiabetic [19], and protein kinase inhibitor [20], literature survey reveals that so many of the natural and synthetic thiazole and pyrazole chalcones possess large number of pharmaceutical activities. Due to the importance and in continuation of our work on synthesis of biologically important molecules [21], here, we designed and synthesized various thiazolepyrazole integrated chalcones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%